2 coelhos: um olhar sobre as possibilidades intertextuais e híbridas na produção cinematográfica contempoarânea - Fabricio, Evandro Klos (2016)
The abundant use of digital technology for recording and edition has become evident, allowing a transformation in how to see and how to do cinema. The technical enhancements pushed further not only the producing way, but also how the audiovisual language in which it is presented, creating new aesthetical possibilities. This research proposes an approach to a cinematographic piece which uses those elements in its composition. Regarding this whole aspect, the choice of the theme of the corpus was a piece of the Contemporaneum Brazilian Cinema, a specific cut was chosen for empiric aim: Afonso Poyart’s 2 Coelhos, 2012 (2 Rabbits). Studying the fact that the selection and organization of the opus is to be used as corpus empiricus of this research, some questions are made: How do the new technological path and the infiltration of hybrid intertextual languages contribute to the upgrade process of the narrative line of the referred movie, in a right way distancing it from others contemporaneous Brazilian pieces, regarding its structure, and inserting it in the rol of productions of a contemporaneous movie? It is expected that the use of new technological environment, added to the use of different forms of audiovisual language as a whole – artistic genre, graphic art, graphics for games – indicates an advance in cinematographic production nowadays. As General Objective, it is intended to identify in 2 Coelhos the use of intertextual hybrid language, delivered as a result of the use of the new digital technology in the making of new ways of showing audiovisual elements in the movie. As Specific Objectives: to explore the narrative voice present in the movie; to define what is seen for polifony, dialogism and intertextuality, through historical perspective; to list the concepts of hybrid language seen in movie-making; to analyze the intertextuality present in the production, by comparing visual elements of the movie which have reference from other midia and art; to identify the construction of hybrid images by the intersection of new technological parafernalia from other audiovisual media – games, visual arts and animation. For the critic analyzis, in its own intertextual way, it is supported by authors like Jean Pouillon, Normam Friedman and Ligia Chiappini Moraes Leite, related to the narrative focus; of the linguistic concept oriented by Mikhail Bakthin, about monological, dialogical and polifonic texts; Julia Kristeva’s text about intertextuality; as theoritical advisors about cinema and new technologies: Arlindo Machado, Ismail Xavier, Jacques Aumont, André Bazin, Noel Burch, David Bordwell, Kristin Thompso, Robert Stan. To list, in Poyart’s movie, these characteristics – intertexuality, hybridization and new tchnologies – it was necessary to identify and separate, inside the vast visual array of the film, six scenes (or sequences). The option of use of these specific pieces was both dinamic and efficient, to answer the first raised questions. At last, it is understood that the insertion of hybrid intertextual language, added to the use of new technology in its womb, is determinating factor of a huge enhancement in the motion of the movie. Otherwise it would be just one more production of the genre.